Research from low-income and middle-income countries will benefit global health and the physiotherapy profession, but it requires support - Saurab Sharma; Arianne Verhagen; Mark Elkins; Jean-Michel Brismee; George D. Fulk; Jacub Taradaj; Lois Steen; Alan Jette; Ann Moore; Aimee V. Stewart; Barbara J. Hoogenboom; Anne Soderland; et al. (AOSIS, 2023)
No abstract available.